SYNTHESIS, SPECTRAL, THERMAL, ANTI MICROBIAL AND CATALYTIC ACTIVITY OF Zn2+ AND Cd2+ CHELATES WITH VALSARTAN. - PARASHAR H.MODH,; PARASHAR H.MODH,; JABALI J. VORA, (International Journal of Pharma and Bio Sciences, 2014)
The metal chelates of Zn2+ and Cd2+were prepared and characterized by physico- chemical analyses, Elemental analysis, UV - visible, IR, NMR and Thermal analyses. The probable structure has been assigned based on the above analysis. These complexes were used as catalyst for some selected redox and organic reactions. The antimicrobial activity of the ligand and their metal chelates were screened against various bacteria and fungi.